2018
DOI: 10.1097/wnr.0000000000001097
|View full text |Cite|
|
Sign up to set email alerts
|

Dysregulation of bcl-2 enhanced rotenone-induced α-synuclein aggregation associated with autophagic pathways

Abstract: α-Synuclein (α-syn) aggregation has far-reaching implications in the pathogenesis of Parkinson's disease, and the levels of α-syn protein determine its neurotoxic potential. However, the intrinsic pathway of α-syn accumulation and the mode of α-syn degradation remain contentious. Following a stereotactic infusion of rotenone into the substantia nigra and the ventral tegmental area, the chronic rat model of Parkinson's disease was established successfully. In response to the rotenone, increased intracellular α-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Alpha-syn aggregate is a critical event in the death of DA neurons and the progression of PD (Sanders and Greenamyre, 2013). Rotenone is an insecticide, which could inhibit complex I activity and promote α-syn up-regulation and aggregate (Betarbet et al, 2000;Sanders and Greenamyre, 2013;Chen et al, 2018). Our results also indicate that rotenone is able to increase both the mRNA and protein levels of α-syn in SH-SY5Y cells.…”
Section: Discussionsupporting
confidence: 58%
“…Alpha-syn aggregate is a critical event in the death of DA neurons and the progression of PD (Sanders and Greenamyre, 2013). Rotenone is an insecticide, which could inhibit complex I activity and promote α-syn up-regulation and aggregate (Betarbet et al, 2000;Sanders and Greenamyre, 2013;Chen et al, 2018). Our results also indicate that rotenone is able to increase both the mRNA and protein levels of α-syn in SH-SY5Y cells.…”
Section: Discussionsupporting
confidence: 58%
“…α-Synuclein aggregation increased, accompanied by reduction of BCL-2 level and blockage of autophagic flux, in dopaminergic neurons of rotenone-induced PD rats. While inhibition of BCL-2 could aggravate autophagic insults and increase rotenone-induced α-synuclein aggregation, indicating dysregulation of BCL-2 enhanced rotenone-induced neurotoxin . One study found that BAX is translocated to and internalized by lysosomes following MPTP treatment and that inhibiting BAX could restore lysosomal function and reverse autophagosome accumulation, suggesting that BAX contributes to lysosomal disruption in MPTP-induced PD models .…”
Section: Pdmentioning
confidence: 99%
“…While inhibition of BCL-2 could aggravate autophagic insults and increase rotenone-induced α-synuclein aggregation, indicating dysregulation of BCL-2 enhanced rotenone-induced neurotoxin. 106 One study found that BAX is translocated to and internalized by lysosomes following MPTP treatment and that inhibiting BAX could restore lysosomal function and reverse autophagosome accumulation, suggesting that BAX contributes to lysosomal disruption in MPTP-induced PD models. 107 Restoring autophagy through modulation of BCL-2 is another potential therapeutic strategy for PD treatment.…”
Section: ■ Autophagymentioning
confidence: 99%
“…The rotenone model stands out from other toxin-based models by replicating almost all the features of Parkinson’s disease including α-synuclein aggregation and Lewy-like body formation (Sherer et al , 2003; Yuan et al , 2015; Chen et al , 2018). Among the toxic animal models of Parkinson’s disease, rotenone represents one of the most used approaches.…”
Section: Discussionmentioning
confidence: 99%